Real‐time analysis of switchable nanocomposites of magnesium pyrophosphates and rolling circle amplification products. Issue 8 (21st April 2020) - Minero, Gabriel Antonio S.; Fock, Jeppe; Tian, Bo; Rizzi, Giovanni; Neumann, Felix; Madaboosi, Narayanan; Nilsson, Mats; Fougt Hansen, Mikkel
Abstract: Rolling circle amplification (RCA) is a robust isothermal nucleic acid amplification method producing nanocomposites of DNA and inorganic magnesium pyrophosphate precipitates. Although the conformation and structure of such nanocomposites impact applications, most studies of them have been performed at the end‐point after exposure to a treatment. Here, we use real‐time optomagnetic measurements of the hydrodynamic size of magnetic nanoparticles (MNPs) to study the growth of RCA products grafted onto MNPs as well as the effect of post‐RCA temperature annealing and chemical treatment. As a key result, we show that secondary structures in the RCA products trap and partially protect magnesium pyrophosphate precipitates and that these are reversibly released upon heating above a characteristic temperature defined by the sequence of the RCA product. These findings provide a deeper mechanistic understanding of the synthesis and structure of DNA nanocomposites, which impacts applications of DNA nanocomposites in sensing and drug delivery. Abstract : Self‐annealing of long single stranded DNA amplicons drives their supramolecular assembly on the surface of magnetic nanoparticles as well as inclusion of magnesium pyrophosphate precipitates during rolling circle amplification. Post‐RCA temperature annealing cycles result in reversible release and re‐capture of the pyrophosphates at a characteristic temperature linked to the GC content of the DNA amplicons. The transition is dramatically altered/ absent upon magnetic separation or treatment with EDTA or pyrophosphatase enzymes prior to the temperature annealing.